Taper optimization for small billet moulds - CAO Yi-fei; ZHANG Jiong-ming; WANG Bo (工程科学学报)
A finite element model to describe the solidification and heat transfer process and the elastoplastic deformation in a mould is built by using the commercial software Thercast to study the thermomechanical behavior of the billet. Firstly, applying the heat flux on the billet shell surface, we obtain the solidification shrinkage and the shell temperature distribution of the billet, analyze the effect of molten steel static pressure, and propose the taper design principle of the mould to determine an appropriate mould taper profile. Then, applying the water cooling heat transfer coefficient on the cold side of the mould and considering the effect of casting slag and gap on the solidified shell, we study the solidification process of billet shell in the mould, and thus verify the rationality of taper design.